2021
DOI: 10.1089/aivt.2020.0022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Biological Effects of Novel Tobacco Product Vapor Using Two- or Three-Dimensional Culture Systems of Human Bronchial Epithelia

Abstract: Introduction: Because of the rising popularity of novel tobacco products, there has been an increasing interest in the biological effects of these products. This study was performed to investigate the biological effects of vapor from a novel tobacco vapor product (NTV) in comparison with cigarette smoke (CS) from a 3R4F reference cigarette by using two types of in vitro model. Materials and Methods: A two-dimensional (2D) culture system composed of a submerged monolayer of BEAS-2B cells was used to detect cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Furthermore, the repeated exposure element of the study more accurately models likely human exposure patterns than a single, acute, in vitro exposure ( Mallock et al, 2019 ; Jones et al, 2020 ; Laverty et al, 2021 ). Interestingly, lower or absent responses in 3D respiratory tissue models exposed to heated tobacco aerosol, compared to cigarette smoke, in the short term (e.g., up to 72 h), following an acute exposure ( Iskandar et al, 2018 ; Mori et al, 2021 ) was a relative response observed to be maintained over the 28 days of the current study. The findings of the current study therefore indicate reduced harm potential of the p-HTPs over the longer period tested.…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, the repeated exposure element of the study more accurately models likely human exposure patterns than a single, acute, in vitro exposure ( Mallock et al, 2019 ; Jones et al, 2020 ; Laverty et al, 2021 ). Interestingly, lower or absent responses in 3D respiratory tissue models exposed to heated tobacco aerosol, compared to cigarette smoke, in the short term (e.g., up to 72 h), following an acute exposure ( Iskandar et al, 2018 ; Mori et al, 2021 ) was a relative response observed to be maintained over the 28 days of the current study. The findings of the current study therefore indicate reduced harm potential of the p-HTPs over the longer period tested.…”
Section: Discussionmentioning
confidence: 52%
“…Oxidative responses were also assessed using immortalized normal human bronchial epithelial cells in an ARE reporter assay that detects nuclear factor-erythroid 2-related factor-2-mediated oxidative stress responses [35] , [36] , like in previous studies [31] , [32] , [37] .…”
Section: Resultsmentioning
confidence: 99%
“…New approach methodologies (NAMs), which include in silico , in chemico , in vitro , and ex vivo approaches [47] , [48] , are being rapidly developed because of, while not yet fully validated their potential to reliably reflect human biology [49] . Recently, the 3D bronchial epithelial model has been applied as mechanistic follow-up in vitro toxicity comparison among CS and THS2.2 [50] , THP1.0 [51] , [52] , or the other type of HTP [31] , [53] , [54] . These assessments using NAMs such as human 3D tissue models, once fully validated, would also contribute to the examination of reduced risk potential of DT3.0a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation